Admixture mapping analysis reveals differential genetic ancestry associated with Chagas disease susceptibility in the Colombian population. Issue 24 (23rd July 2021) - Casares-Marfil, Desiré; Guillen-Guio, Beatriz; Lorenzo-Salazar, Jose M; Rodríguez-Pérez, Héctor; Kerick, Martin; Jaimes-Campos, Mayra A; Díaz, Martha L; Estupiñán, Elkyn; Echeverría, Luis E; González, Clara I; Martín, Javier; Flores, Carlos; et al.
Abstract: Chagas disease is an infection caused by the parasite Trypanosoma cruzi, endemic in Latino America. Leveraging the three-way admixture between Native American (AMR), European (EUR) and African (AFR) populations in Latin Americans, we aimed to better understand the genetic basis of Chagas disease by performing an admixture mapping study in a Colombian population. A two-stage study was conducted, and subjects were classified as seropositive and seronegative for T. cruzi . In stage 1, global and local ancestries were estimated using reference data from the 1000 Genomes Project (1KGP), and local ancestry associations were performed by logistic regression models. The AMR ancestry showed a protective association with Chagas disease within the major histocompatibility complex region [Odds ratio (OR) = 0.74, 95% confidence interval (CI) = 0.66–0.83, lowest P -value = 4.53 × 10 −8 ]. The fine mapping assessment on imputed genotypes combining data from stage 1 and 2 from an independent Colombian cohort, revealed nominally associated variants in high linkage disequilibrium with the top signal (rs2032134, OR = 0.93, 95% CI = 0.90–0.97, P -value = 3.54 × 10 −4 ) in the previously associated locus. To assess ancestry-specific adaptive signals, a selective sweep scan in an AMR reference population from 1KGP together with an in silico functional analysis highlighted the Tripartite Motif family and the human leukocyte antigen genes, with crucial role in the immune response against pathogens. Furthermore, these analyses emphasized the macrophages, neutrophils and eosinophils, as key players in the defense against T. cruzi . This first admixture mapping study in Chagas disease provided novel insights underlying the host immune response in the pathogenesis of this neglected disease.